Optical and electrical characterisation of hexabenzocoronene derivative molecular self-assemblies - Fleming, Alexander (Trinity College (Dublin, Ireland). School of Physics, 2006)
In this thesis the optical properties of molecular aggregates of Hexa-peri-benzocoronene derivatives are investigated for evidence of Frenkel Exciton Resonance (FER). Using photo-luminescence and optical absorption measurement techniques the HBC derivatives are observed, in the optical spectra, to aggregate in solution to form ordered Molecular Self-Assemblies (MSAs). The change from isolated to aggregated form gives rise to spectroscopic signatures that are best explained by FER. The determination that the low concentration species is the isolated molecule allows the photo-physics of isolated and aggregated molecules to be compared.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin